2017
DOI: 10.1007/s00167-017-4775-4
|View full text |Cite
|
Sign up to set email alerts
|

Return to sports after the latarjet procedure: high return level of non-collision athletes

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 21 publications
(30 reference statements)
2
60
0
Order By: Relevance
“…The 14 studies analyzed in the systematic review included 883 patients. [2][3][4][5][6][7][8]10,11,14,[16][17][18]21 The studies were primarily level 3 (n = 4) or level 4 (n = 10) evidence; of the 14 studies, 13 had a MINORS score greater than 80%. Of the studies that reported the participants' sex, the majority were male (88%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 14 studies analyzed in the systematic review included 883 patients. [2][3][4][5][6][7][8]10,11,14,[16][17][18]21 The studies were primarily level 3 (n = 4) or level 4 (n = 10) evidence; of the 14 studies, 13 had a MINORS score greater than 80%. Of the studies that reported the participants' sex, the majority were male (88%).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [2][3][4][5]8,11,14,17,18,21 reported return to sport at any level (Table 2 and Appendix Figure A1, available online), which ranged from 80% to 100% with the exception of 1 study (38%). 8 Eleven studies 2,3,6,7,10,11,14,[16][17][18]21 reported return to sport at the previous level of play (Table 2 and Appendix Figure A2, available online), which ranged from 56% to 95% with the exception of 1 study (16%). The average time for return to sport ranged from 3.2 to 8.1 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations